INTEGRATING CRIMINOLOGICAL PERSPECTIVES: THE OVERLOOKED ROLES OF LAND AND RELIGION IN CRIME CAUSATION - Ohiomah, Ajayi; Efejuku, Amorighoye Deston; Udeh, Promise Chinedu (African Journal of Social and Behavioural Sciences, 2026)
The study analyses the evolution of criminological theories and their impact on global penal systems, addressing the requirement for an integrated analysis of crime causation. Grounded in the Evolutionary Model, the research examines how shifting definitions of the criminal actor dictated social policy from eighteenth-century Classical thought to contemporary Situational theories. Using a qualitative meta-synthesis design involving a three-tier coding protocol of a corpus of 120 foundational theoretical texts and thematic analysis deconstructed the relationship between the individual and the state. The findings identified four primary clusters: Internalised Determinism, Socio-Structural Failure, Hegemonic Power, and Situational Convergence. This indicates a historical shift from biological conceptualisations to systemic and environmental failures. The research attempts to address identified gaps in mainstream sociology by suggesting that land tenure and religious interaction serve as significant triggers for systemic violence. Results suggest that criminal behaviour arises from specific situations conducive to deviance rather than inherent defects. The study concludes that sustainable crime reduction requires a multi-disciplinary framework addressing root structural causes. It recommended policy measures that transition from punitive justice toward holistic structural support and environmental design.